The Environmental and Economic Impact of Applying Radiant Slabs Technology in Syria - كنجو عماد الدين; ابو علي اماني (Latakia University Journal -Engineering Sciences Series, 2021)
In Syria, buildings often lack thermal design and Heating, Ventilating, and Air Conditioning systems, and they are being replaced by solutions that do not provide thermal comfort and damage the environment. The pursuit of thermal comfort, the high price of fuel and the increased awareness of its negative impact on the environment are guide reasons for considering solutions that cause less environmental damage, and provide the required thermal comfort at the lowest cost. In this research, the radiant slabs technology was studied as an alternative that will be compared with traditional case in Syria (Hourdi slabs and the radiators system) in terms of the costs during the building life cycle and the emission of harmful gases to the environment. The study proved that the radiant slabs in comparison with traditional case were able to reduce the life cycle costs of studied buildings by an annual average of about 860 Sp/m2 at an exchange rate 400 Sp/, while they increased the amount of harmful gases that emitted to the environment slightly by annual averages of about: (2.4, 0.0003, 0.03, 0.006) kg/m2 for each of the following gases: (CO2, CO, SO2, NOX), respectively.